Pengaruh Deep Breathing Exercise Terhadap Tingkat Kecemasan Pada Pasien Pre Operasi Sectio Caesarea Di Rumah Sakit Lavalette Kota Malang - Hidayat Abdul Azis; Ekowati Retnaningtyas; Goretti Maria Sindarti (Jurnal Pendidikan Kesehatan, 2020)
Deep Breathing Exercise is one of the nonpharmacological management that is an effective method of reducing anxiety in patients undergoing surgery. The purpose of this study is to determine the effect of Deep Breathing Exercise on anxiety levels in patients pre surgery Sectio Caesarea at Lavalette Hospital of Malang. The research design used was pre experimental design with one group pretest postest design. The sample in this research is 26 respondents. Sampling using purposive sampling, data collection using questionnaires and interviews using the HARS scale. The result of this research was obtained pretest data of Deep Breathing Exercise of anxious patient very heavy 4 people namely 15,38 percent, worried weight 17 people namely 65,38 percent, anxious being 5 people namely 19,24 percent. Posttest Deep Breathing Exercise patient anxious weight 12 people namely 46,15 percent, anxious being 11 people namely 42,31 percent, mild anxious 3 people namely 11,54 percent. Based on the results of the research analysis using Wilcoxon Sign Rank Test, the results showed that p value equal 0.001 is smaller than p equal 0.05, it can be concluded that there is influence of Deep Breathing Exercise on anxiety level in patient pre operation of Sectio Caesarea at Lavalette Hospital of Malang. The researcher recommendation is then expected to use more samples and longer treatment. So that will cause a greater effect on decreasing anxiety levels of patients preoperative Sectio Caesarea.